A review of SaiLuoTong (MLC-SLT) development in vascular cognitive impairment and dementia - Ampil, Encarnita Raya; Ong, Paulus Anam; Krespi, Yakup; Yang, Yuan-Han (Frontiers in Pharmacology, 2024)
The dementia epidemic, attributed to aging populations, represents a growing socio-economic burden. There are various cause of dementia, including mixed dementia combining Alzheimer's Disease (AD) and Vascular Dementia (VaD). Vascular Cognitive Impairment and Dementia (VCID) designates the full spectrum of cognitive dysfunction of vascular origin. We reviewed epidemiological, pathophysiological and clinical data on VCID with a focus on VaD, as well as key data on the development of a new therapeutic solution, SaiLuoTong (MLC-SLT). From documentary research executed on different web sources (PubMed, Clintrials.gov, Z-library and Google), our initial selection for the short review of VCID and VaD was based on keywords contained in each paragraph subtitles of this article with exclusion of publications in a language other than English or published before 2010. Sorted by relevance and publication date, 47 references were selected from 140 shortlisted for review. No drugs are approved for the treatment of VaD by major Western regulatory agencies, while some traditional Chinese medicines (TCMs) are registered in China. VCID treatment should have a dual focus: managing the underlying cerebrovascular hypoperfusion disease and dementia-related symptoms. This is the objective set for the development of the MLC-SLT, the essential data of which are reviewed in detail. In two VaD clinical trials, MLC-SLT improved cognitive symptoms and activities of daily living, with good safety and potential disease modifying effect. In a placebo-controlled study in 325 patients with mild to moderate VaD diagnosis and randomized according to a delayed-start design, MLC-SLT demonstrated significant improvement in memory tests and performance in executive function tasks, expanding its place in the management of VCID. At week 26, changes in VADAS-cog scores (SD) from baseline were 23.25 (0.45) for MLC-SLT 180mg bid), 23.05 (0.45) for MLC-SLT 120mg bid (both p<0.0001), and 20.57 (0.45) for placebo (p=0.15). At week 52, differences between both groups MLC-SLT and placebo were 2.67 and 2.48, respectively (p<0.0001), without significant difference between MLC-SLT groups. MLC-SLT (SaiLuoTong) is a useful and promising addition in the management of VaD by taking part in the success of the struggle against the condition, which remains limited to date.